The emergence of Dengue Fever in Sheikhupura, Pakistan: its seroprevalence and risk factors assessment during 2014-2017 - Muhammad Uzair Mukhtar; Maria Mukhtar; Naveed Iqbal; Zeeshan Nawaz; Adil Bhatti; Fatima Haq; Ali Arslan; Muhammad Rashid (Journal of Infection in Developing Countries)
Introduction: District Sheikhupura encountered its first dengue outbreak in 2014 but lacked serological evidence and reports of risk factors associated with it. To assess this, a hospital-based study was conducted from January 2014 to December 2017.